2018
DOI: 10.1002/jcsm.12274
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative sarcopenia and post‐operative accelerated muscle loss negatively impact survival after resection of pancreatic cancer

Abstract: BackgroundSarcopenia and post‐operative accelerated muscle loss leading to cachexia are commonly observed in patients with pancreatic cancer. This study aimed to assess the influence of body compositions and post‐operative muscle change on survival of patients with surgically treated pancreatic cancer.MethodsWe analysed data of patients diagnosed with pancreatic adenocarcinoma who underwent surgery from 2008 to 2015. Skeletal muscle areas, muscle attenuation, and visceral and subcutaneous adipose tissue areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
150
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(158 citation statements)
references
References 41 publications
2
150
3
3
Order By: Relevance
“…Evaluating muscle at a single specific time point may not help in predicting survival and could not evaluate muscle loss . These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating muscle at a single specific time point may not help in predicting survival and could not evaluate muscle loss . These findings suggested that a longitudinal study of changes in body composition may provide a more comprehensive understanding of the impacts of body composition on outcomes …”
Section: Discussionmentioning
confidence: 99%
“…In this study, SMD at baseline was negatively correlated with BMI and TATI and weakly correlated with SMI ( Figure S3). We defined our own cut‐off values for our cohort based on previous studies with similar population sizes . Using the present cut‐off value of SMD, the myosteatosis group had significantly higher adipose tissue indexes and non‐significantly higher BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with end-stage liver disease and awaiting transplantation, a model including sarcopenia could even surpass the MELD score in predicting waiting list mortality [54]. A variety of studies [19,30,32] have also explored the role of sarcopenia in the occurrence of complications in patients undergoing hepatopancreatobiliary surgery. In these studies, sarcopenia was defined by various indexes; however, the conclusions drawn from different studies and various indexes have remained controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies [11,13,[20][21][22][23] [32], and 1 in China [26]. Among the included studies, 13 studies were directed at liver [11,13,[19][20][21][22][23][24][25][26][27][28][29] malignancy, 2 bile duct [30,31], 6 pancreas [12,14,[32][33][34][35], 2 periampullary [36,37], 4 periampullary and pancreas [38][39][40][41], and 1 hepatopancreatobiliary [42]. The sample size ranged from 67 to 763.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…15 The effects of body compositions on post-operative longterm outcomes have been reported in patients with pancreatic cancer and hepatocellular carcinoma. 16,17 In case of biliary tract cancer, there have been a few studies analysing the relationship between prognosis and body composition, limited to a specific location of bile duct cancer (i.e. distal, perihilar, or intrahepatic bile ducts).…”
Section: Introductionmentioning
confidence: 99%